Mush! : sled dogs of the Iditarod - Funk, Joe (Scholastic Inc., 2013)
"From one of the coldest regions on earth come the mighty sled dogs of the Iditarod. With long hours, freezing temperatures, and treacherous climbs, discover how the mushers and their amazing dogs manage to complete (and win) this grueling race across Alaska"--P. [4] of cover.